Analysis Of Leading Sector Clusters In Increasing Gross Domestic Products In Sambas District - Ahmad Yasir (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2021)
The researcher aims to reveal the secondary data that Sambas Regency has about the regency's superior potential. Secondary data comes from the time series of Gross Regional Domestic Product (PDRB) of Sambas Regency and West Kalimantan Province 2018-2020. The research method used is quantitative and data analysis using Typology Klassen, Location Quotient (LQ) and Shift Share. Klassen typology was used as a quantitative analysis of secondary data and the results showed that Sambas developed the agricultural and trade sectors, hotels and restaurants. Location Quotient data analysis shows too many sectors of agriculture, trade, hotels and restaurants. Leading sectors in the form of agriculture, mining and quarrying, manufacturing industry, electricity, gas and clean water, construction, trade, hotels and restaurantswere revealed by the researcher using Shift Share. The analysis of this research data shows that in Sambas the trade, hotel and restaurant sectors have become leading sector in the economy.